Greenfield Entry Strategy of Multinational Enterprises in the Emerging Markets: Influences of Institutional Distance and International Trade Freedom. Issue 2 (3rd April 2017) - Arslan, Ahmad; Larimo, Jorma
ABSTRACT: This article addresses greenfield entry strategy of multinational enterprises in emerging markets by analyzing the influences of formal and informal institutional distance as well as international trade freedom. The empirical analysis is based on a sample of 263 greenfield market entries in manufacturing sector undertaken by Finnish firms during 1990–2013. The study results revealed that high formal and informal institutional distances led to the preference of greenfield JVs. The study also found that high level of international trade freedom moderates the influences of formal and informal institutional distances on greenfield entry strategy.